The Influence of Quality Management System and Training on Employee Performance at PT X - Rosmawati Rosmawati; Hariandy Hasbi (Dinasti Publisher, 2025)
The study entitled The Effect of Quality Management Systems and Training on Employee Performance at PT X highlights the importance of improving the quality of human resources through the implementation of effective quality management systems and training programs to support employee performance. The purpose of this study is to examine the effect of quality management systems and training, both partially and simultaneously, on employee performance at PT X. The research method used is a quantitative approach with a survey technique involving 98 respondents. The data collection instrument is a Likert scale questionnaire, which is then analysed using simple and multiple linear regression. The results of the study indicate that the quality management system has a positive and significant effect on employee performance. Similarly, training has a positive and significant effect on employee performance. Furthermore, these two variables together have a positive and significant effect on employee performance. These findings confirm that the implementation of a good quality management system and effective training programs are important factors in improving employee performance at PT X.